Are non-demented patients with Parkinson's disease able to decide about their own treatment?. (May 2017) - Eygelshoven, Sandra; van den Hout, Anja; Tucha, Lara; Fuermaier, Anselm B.M.; Bangma, Dorien F.; Thome, Johannes; Lobbestael, Jill; Tucha, Oliver; Koerts, Janneke
Abstract: Introduction: Patients with Parkinson's disease (PD) are often confronted with difficult medical decisions, which might be hampered by cognitive impairment or chronic stress. Little is known, however, about the capacity to make medical decisions and the influence of cognition and stress on this ability. This study determined whether non-demented Parkinson's disease patients are able to make medical decisions and whether this capacity is influenced by cognition and stress. Methods: Forty-six Parkinson's disease patients and 94 healthy controls were assessed with the MacArthur Competence Assessment Tool for Treatment during which participants were presented with deep brain stimulation as a treatment option for a fictional Parkinson's disease patient. Furthermore, all participants were examined with a stress questionnaire and a neuropsychological test battery. Results: Parkinson's disease patients performed better on the total scale and 'Understanding' subscale of the MacArthur Competence Assessment Tool for Treatment than healthy controls. Lower performance on the Concept Shifting Test in the Parkinson's disease group and lower performance on Letter Digit Substitution Test in the healthy control group predicted lower medical decision-making capacity. No association was found between stress and medical decision-making. Conclusion: Non-demented Parkinson's disease patients show no impairments in medical decision-making compared to healthy controls. In fact, Parkinson's disease patients have a better understanding of their disease and the benefits and risks of treatment options than healthy controls. Psychomotor speed and attention were negatively associated with medical decision-making in both groups. This implies that when these cognitive functions decline, the capacity to make medical decisions also declines. Highlights: Non-demented PD patients show no impairment in medical decision-making (MDM). PD patients have a better understanding of their treatment than healthy controls. A decreased psychomotor speed has a negative influence on MDM in PD.